Changes in movements of white seabream (Diplodus sargus) during the reproductive season - Abecasis, D. (2016)
It has been hypothesized, based on anecdotal information and reports, that adult white seabream migrate and aggregate during spawning. Because most of the past telemetric studies on this ecologically and commercially important species were short in duration and did not cover the reproductive season, we set out to use longer-term passive acoustic telemetry to test this hypothesis. We found that white seabream expands its home range and increases the frequency of forays during the reproductive season, but found no obvious signs of spawning aggregations. Our results thus provide evidence for short-range behavioral shifts in fish space use related to reproductive activity, and support the notion that small MPAs may be effective in managing reef fish populations by effectively protecting their spawning biomass. (c) 2015 Elsevier Ltd. All rights reserved.